European Union defence policy – treaty dimension - Łukasz Potocki (Facta Simonidis, 2017)
Defence policy has recently become one of the components of the external dimension the European Union policy, reflecting, in a sense, on the need to be a strategic player in international relations and not only in economic matters. This article presents the evolution of this policy from the 90s to the present solutions. The starting point is a treaty analysis of the principles presented in each document starting with the Maastricht Treaty to the decision in the Treaty of Lisbon. In addition, the specificity of the EU as an international legal entity, and the procedure for deciding on external issues was shown.